Music Activity as a Communication Tool for Young Autistic Adolescents - Vilkelienė, Aldona; Kondrotienė, Eglė (Pedagogika, 2015)
Music and its influence on personality was for a long time under research and still is contextualized. The task of this work was to disclose possibilities of various music activities and to find out their positive influence for young autistic adolescents’ communication and interaction activities. It was also very important to find the answer to the question, if music interaction is possible for autistics as this disorder prevent ability to communicate and to get into contact with other people. Theoretical part of this piecework deals with the reasons for autistic disorder, manifestations of autism and specifics of communication. Also, here are presented approaches of view of different authors what concerns the music and various music activities in the context of musical methods. On the basis of this theoretical context was executed empirical research with autistic people where, according to the chosen music and usage of it’s methodology, was formulated task to try to reach (cultivate) social communication and socialization capabilities. Empirical research revealed that for young autistic adolescents the most stimulating music activities are music activities: improvisation, singing, also listening to music and movement. Music activities revealed interpersonal relation between young autistic adolescent and pedagogue through more active eye contact; young autistic adolescents started more actively communicate with gestures and body language. Empirical research also displayed that the right choice of the musical method is directly related with the process of education and ensure its success. Also, it was proved that the success of the development of disabled people with communication disorders greatly depends on teamwork, – cooperation among young autistic adolescents, their parents, special educators and social workers. This teamwork cooperation helps to develop communication and cooperation abilities. Research results show that music activities could be (can be) natural process of communication and affiliation for young autistic adolescents.